Thin-film transistor-based micro light-emitting diode circuits for achieving short delay time by controlling operation sequence in mobile displays - Eun Kyo Jung; Han Cheol Lee; Kook Chul Moon; Hwarim Im; Yong-Sang Kim (Journal of Information Display)
This study proposed a micro light-emitting diode (µLED) pixel circuit with a short µLED current (IµLED) delay time for mobile displays. A pixel circuit using complementary metal-oxide-semiconductor-type low-temperature polycrystalline silicon (LTPS) thin-film transistors (TFTs) was designed. The proposed pixel circuit used n-type LTPS TFTs as driving and emission TFTs for pulse width modulation and controlled the µLED operation sequence from the off- to the on-state. Because the pixel circuit’s input signal characteristics could affect the IµLED delay time, the researchers also developed an integrated driver circuit with multiple output signals to operate the proposed pixel circuit. The pixel circuit operations were simulated by connecting the proposed pixel and integrated driver circuits. Consequently, the proposed pixel circuit exhibited a short IµLED delay time of 2.8 µs by enhancing the controllability over the driving TFTs for pulse amplitude modulation during µLED transition. The featured circuits can operate in normal and always-on display modes. The proposed circuits could be integrated into a 320 pixels per inch display based on the layout design. Therefore, the proposed pixel circuit can help improve low gray level expression capability because of the short IµLED delay time and can be used for high-resolution mobile µLED displays.